2021
DOI: 10.1177/25158414211020152
|View full text |Cite
|
Sign up to set email alerts
|

Pterygium: an update on pathophysiology, clinical features, and management

Abstract: Pterygium is a relatively common ocular surface disease. The clinical aspects and the treatment options have been studied since many years ago, but many uncertainties still exist. The core pathologic pathway and the role of heredity in the development of pterygium are still attractive fields for the researchers. The role of pterygium in corneal irregularities, in addition to the refractive properties of pterygium removal, has been increasingly recognized through numerous studies. The association between pteryg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 169 publications
0
60
0
4
Order By: Relevance
“…Analysis of the genomes of thousands of human cancers has revealed that TP53 is inactivated by mutation in over 50% of sporadic human tumors [ 104 ]. At one time, the main pathway for development of pterygium was believed to be mutations in TP53 [ 105 ]. However, this hypothesis has fallen out of favor for a variety of reasons, an important one being that inactivating TP53 mutations could not be detected [ 106 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the genomes of thousands of human cancers has revealed that TP53 is inactivated by mutation in over 50% of sporadic human tumors [ 104 ]. At one time, the main pathway for development of pterygium was believed to be mutations in TP53 [ 105 ]. However, this hypothesis has fallen out of favor for a variety of reasons, an important one being that inactivating TP53 mutations could not be detected [ 106 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two limbal grafts from the 6 and 12 o’clock positions of the healthy contralateral eye are harvested, transplanted and secured to the diseased eye [ 14 ]. The most common use of CLAU has been performed in surgery for pterygium or severe corneal chemical burn [ 216 , 217 ]. In recent years, several studies have reported the long-term ocular surface stability of CLAU in unilateral LSCD [ 218 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%
“…Thus, pterygium excision is one of the most common ophthalmic operations in patients who live in tropics and subtropics [ 2 ]. The bare sclera technique is the first surgical intervention associated with high rates of pterygium recurrence and postoperative infection [ 8 ]. Pseudomonas aeruginosa scleritis is commonly associated with the excision of pterygium and may occur years after surgery.…”
Section: Introductionmentioning
confidence: 99%